Technical and Economic Assessment of Energy Efficiency of Electrification of Hydrocarbon Production Facilities in Underdeveloped Areas - Oksana Marinina; Anna Nechitailo; Gennady Stroykov; Anna Tsvetkova; Ekaterina Reshneva; Liudmila Turovskaya (Sustainability, 2023)
The relevance of the technical and economic evaluation of options for the optimization of electrification projects of hydrocarbon production facilities is due to the growing need for the development of new fields in undeveloped and hard-to-reach territories. Development of new fields requires the construction of large amounts of infrastructure energy facilities, new solutions to improve energy efficiency, reducing capital intensity of projects, solutions to improve the efficiency of resource use in the circular economy, and the use of renewable energy sources (RES). Analysis of the technological directions of electrification of hydrocarbon production facilities proves that the low level of application of RES for energy supply purposes is due to the lack of experimental data on the implementation of this kind of project. This study considers features of technological solutions, practical recommendations, and the main limitations of the application of a hybrid automated system based on RES for the electrification of gas production facilities located in poorly-developed territories. A comparative technical and economic analysis of electrification options using autonomous RES and construction of a power transmission line (PTL) to a remote section of an oil and gas condensate field located in the Arctic zone was carried out. In order to justify the implementation of the electrification project with the use of RES sources, the climatic potential of the region was assessed, and the calculation of energy supply needs and a comparison of alternatives on the basis of specific total capital and operating costs were provided. Assessment of the specific indicator of costs for the proposed variant of the autonomous energy complex based on wind generation indicated savings of RUB 2.24 per kilowatt-hour of energy used. The results of the study can be used in project planning and evaluation of proposed technological solutions based on the rational choice of energy sources and optimization of cost indicators for the construction ...